2016
DOI: 10.1111/ajo.12440
|View full text |Cite
|
Sign up to set email alerts
|

Utility of fetal MRI for workup of fetal central nervous system anomalies in an Australian maternal-fetal medicine cohort

Abstract: MRI added significant diagnostic information in about half the cases referred for workup of suspected CNS anomaly. In six of 17 cases where MRI worsened prognosis, TOP was chosen. Both additional CNS and non-CNS anomalies were diagnosed postnatally in 20%, emphasising the uncertain prognosis for, and evolution of, suspected CNS anomaly in fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…In recent years, MRI has been recommended as a supplement to routine ultrasound for fetal assessment, due to its increased accuracy. 13,14 Compared with previous reports, 15 we observed a higher incidence of accompanying anomalies among cases of mild VM because soft markers, polyhydramnios, and oligohydramnios were regarded as anomalies. We found that most of the intracranial anomalies, which have been reported to be responsible for postnatal morbidity and mortality, 16 accompanied moderate and severe VM.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In recent years, MRI has been recommended as a supplement to routine ultrasound for fetal assessment, due to its increased accuracy. 13,14 Compared with previous reports, 15 we observed a higher incidence of accompanying anomalies among cases of mild VM because soft markers, polyhydramnios, and oligohydramnios were regarded as anomalies. We found that most of the intracranial anomalies, which have been reported to be responsible for postnatal morbidity and mortality, 16 accompanied moderate and severe VM.…”
Section: Discussioncontrasting
confidence: 61%
“…Therefore, differentiation between IVM and NIVM is important. In recent years, MRI has been recommended as a supplement to routine ultrasound for fetal assessment, due to its increased accuracy …”
Section: Discussionmentioning
confidence: 99%
“…According to Malinger et al, neurosonography is equal in its diagnostic capabilities to MRI [28], especially and specifically in the hands of highly proficient neurosonographers. Other groups describe the clinical usefulness of MRI in this context as ranging from 7.9 % to 48 % [29,30]. In our cohort, more than one third of the patients benefited from a clinically significant change in management following their MRI examination.…”
Section: Discussionmentioning
confidence: 67%
“…Fetal MRI is helpful in these scenarios for diagnostic confirmation and in revealing associated cerebral anomalies . However, fetal MRI findings do not replace the gold standard of postnatal diagnosis, which is a weakness that we acknowledge.…”
Section: Discussionmentioning
confidence: 96%
“…Despite adding the CSP ratio to our study parameters, it is nota- Fetal MRI is helpful in these scenarios for diagnostic confirmation and in revealing associated cerebral anomalies. 22,23 However, fetal MRI findings do not replace the gold standard of postnatal diagnosis, which is a weakness that we acknowledge. Given the high proportion of terminated pregnancies with inherent damage to brain tissue, we could not acquire postnatal imaging in all instances.…”
Section: Discussionmentioning
confidence: 97%